Contralateral posterior interosseous flap used to cover large soft tissue defect in the fingers. A case report - Mohd Yusof, Nazri; Zakaria@Mohamad, Zamzuri; Khalid, Kamarul Ariffin; Mohd Amin, Azril; Zulkifly, Ahmad Hafiz; Che Ahmad, Aminudin; Awang, Mohd Shukrimi (Faculty of Medicine, International Islamic University Malaysia, 2007)

(untitled)
Posterior interosseus artery flap is commonly used as a pe dicle flap to cover soft tissue defect in the dorsum of the hand. It is not able to cover a soft tissue defect beyond the level of proximal phalang unless it is used as a free flap. We illustrate 2 cases in which large soft tissue defect in the finger was able to close by using a contralateral posterior interosseous flap. This technique is a reliable alternative method for closing large soft tissue defect in the fingers